HUBUNGAN PENCAHAYAAN DAN SHIFT KERJA TERHADAP KELELAHAN KERJA PERAWAT DI UNIT GAWAT DARURAT RSUD BAA KABUPATEN ROTE NDAO TAHUN 2008 - Sjioen, Maurits; Junias, Marlyn; Ruliati, Luh Putu (Pergizi Pangan DPD NTT, 2010)
The objective of the research is to investigate the relationship between the lighting and working shift, and the fatigue work of the nurses in the Emergency Unit at RSUD Baa Sub District the Regency of Rote Ndao in 2008. It is observational-analytic research by using the design of the cross-sectional study. The population of this research is all 10 nurses in the Emergency Unit at RSUD Baa Sub District the Regency of Rote Ndao. This population is also a sample of this research. This research applies Phi-Coefficient of Association as the statistical test to test the relationship between lighting and fatigue work, and also to Contingency Coefficient Test to test the relationship between shift work and fatigue work. The result of the research shows that there is a relationship between lighting and fatigue work of nurses in the Emergency Unit at RSUD Baa Sub District the Regency of Rote Ndao in 2008 with p = 0,033. Moreover, there is a relationship between shift work and fatigue work of nurses in the Emergency Unit at RSUD Baa Sub District the Regency of Rote Ndao in 2008 with p = 0,040.